2022
DOI: 10.1016/j.cmi.2021.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and fungal bloodstream infections in solid organ transplant recipients: results from a Danish cohort with nationwide follow-up

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Similarly, the Spanish cohort study RESITRA reported highest incidence rates of bacteraemia in lung and pancreas transplant recipients 14 . In contrast, a Danish national cohort study reported higher incidence of bacteraemia in liver and kidney SOTr as compared to other SOT categories 15 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, the Spanish cohort study RESITRA reported highest incidence rates of bacteraemia in lung and pancreas transplant recipients 14 . In contrast, a Danish national cohort study reported higher incidence of bacteraemia in liver and kidney SOTr as compared to other SOT categories 15 …”
Section: Discussionmentioning
confidence: 97%
“…14 In contrast, a Danish national cohort study reported higher incidence of bacteraemia in liver and kidney SOTr as compared to other SOT categories. 15 Most BJI were rather late post-transplant complications, with the exception of thoracic organ transplant recipients, who developed an infection within the 1st year post-transplant, predominately nonvertebral osteomyelitis. In fact, when we looked at time to infection for thoracic (heart and lung) versus abdominal (liver, kidney, kidneypancreas) transplant recipients, BJI occurred significantly earlier in the former (median 5.5 months, IQR: 1-14 versus 22 months, IQR: 10.5-54.5; p = .0001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the immunosuppressive drugs used for the prevention and therapy of rejection event, immune function was impaired and the risk of infection was increased in SOT recipients. 34 In a single-center cohort of kidney transplantation with carbapenem-resistant Klebsiella pneumoniae (CRKP) infection, recipients in the CAZ/AVI therapy group had better clinical outcomes than those in the other antibiotic regimens group, demonstrating the effectiveness of CAZ/AVI. 35 Moreover, another retrospective study evaluated the efficacy of CAZ/AVI in liver transplant recipients with CRKP infection, and showed the clinical benefit of CAZ/AVI with promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the immunosuppressive drugs used for the prevention and therapy of rejection event, immune function was impaired and the risk of infection was increased in SOT recipients. 34 In a single- 35 Moreover, another retrospective study evaluated the efficacy of CAZ/AVI in liver transplant recipients with CRKP infection, and showed the clinical benefit of CAZ/AVI with promising results. 29 Besides, patients who underwent lung transplantation with XDR-GNB infection were reviewed.…”
Section: Discussionmentioning
confidence: 99%